1989
DOI: 10.1063/1.102230
|View full text |Cite
|
Sign up to set email alerts
|

Nitridation-induced surface donor layer in silicon

Abstract: Thin (11.4 nm) gate quality silicon dioxide films were subjected to high-temperature (850–1150 °C) rapid thermal nitridation cycles in ultrapure ammonia. Secondary-ion mass spectroscopy and neutron depth profiling results indicate a significant level of nitrogen diffusion into the silicon substrate. After stripping the dielectric layers, Schottky diode studies were performed using an electrolyte-based technique. We found, for the first time, the formation of nitridation-induced ultrathin (less than 60 nm) n-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…[10][11][12][13] Several recipes, mainly consisting of annealing in NH 3 or N 2 O, have been proposed in literature. 3,5,6,[14][15][16][17] It has been shown that NH 3 nitridation incorporates in the oxide a high amount of nitrogen, resulting in a strong barrier to boron and reduction of oxygen vacancies. Nevertheless, such a process leads to generation of many hydrogen-related charge traps.…”
mentioning
confidence: 99%
“…[10][11][12][13] Several recipes, mainly consisting of annealing in NH 3 or N 2 O, have been proposed in literature. 3,5,6,[14][15][16][17] It has been shown that NH 3 nitridation incorporates in the oxide a high amount of nitrogen, resulting in a strong barrier to boron and reduction of oxygen vacancies. Nevertheless, such a process leads to generation of many hydrogen-related charge traps.…”
mentioning
confidence: 99%